2004
DOI: 10.1080/1364557032000081654
|View full text |Cite
|
Sign up to set email alerts
|

Ratings and rankings: reconsidering the structure of values and their measurement

Abstract: His other recent publications on values have appeared in Social Science Quarterly ('Race, class and gender differences in high school seniors' values ', Vol. 82) and Sociological Perspectives ('Suggestions of the postmodern self ', Vol. 46). He is also active in research on urban racial inequality in the United States.Despite extensive discussion and analysis over the past three decades, researchers are still divided over the preferability of rating or ranking systems for measuring values. However, the debate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 23 publications
0
53
0
2
Order By: Relevance
“…This study provides insight into the cross-national applicability of rating and ranking procedures. Moreover, with this study we respond to the call for further research on this subject made by Ovadia (2004), who suggested comparing a full ranking of values with a rating of the same values.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…This study provides insight into the cross-national applicability of rating and ranking procedures. Moreover, with this study we respond to the call for further research on this subject made by Ovadia (2004), who suggested comparing a full ranking of values with a rating of the same values.…”
Section: Introductionmentioning
confidence: 74%
“…In addition, some studies report higher test-retest reliabilities for ranking (Johnson, Sallis, & Hovell, 1999;Rankin & Grube, 1980), and others for rating (Barylko-Pikielna et al, 2004). The ongoing debate concerning the choice between rating and ranking was characterized by Ovadia (2004) as the rating-ranking impasse. To escape this impasse, we shall approach the problem from a different angle.…”
Section: Rating Versus Rankingmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies were aimed at assessing whether ranking or rating scales produce similar results and at determining which of the scales is preferable (Maio, Roese, Seligman & Katz, 1996), while others pointed out alternatives (McCarty & Shrum, 2000). Discussion of the studies resulted in the argument that each method might represent personal value systems in a specific way (Ovadia, 2004).…”
mentioning
confidence: 99%